Pengaruh Arah Aksial, Keberadaan Buku Dan Ruas Terhadap Kadar Air Dan Berat Jenis Bambu Dikawasan HKm Desa Aik Bual - Radjali Amin; Febriana Tri Wulandari (Agriculture Faculty of Flores University, 2023)
Among the community, bamboo is well known for its excellent utilization, starting from its sturdy, resilient, straight stems, which are easy to split, work with, and shape. In addition, the price of bamboo is cheaper and easily found in residential areas. One of the bamboo-producing areas found in the West Nusa Tenggara region is the Aik Bual Village HKm. It is known that research related to the physical properties of bamboo has not been carried out in the area. Physical properties become a benchmark in seeing cracks and breaks in bamboo caused by high water content and low specific gravity. This study aims to review the four types of bamboo in the Aik Bual HKm area against the influence of axial direction, the presence of books and internodes, moisture content and specific gravity. Fresh water content of petung bamboo, ampel bamboo, string bamboo, galah bamboo: 90,19%; 102,72%; 122,70%; 138,95%. Air dry moisture content of petung bamboo, ampel bamboo, string bamboo, galah bamboo: 12,31%; 13,80%; 12,27%; 11,95. Fresh specific gravity of petung bamboo, ampel bamboo, string bamboo, galah bamboo: 0,63; 0,58; 0,52; 0,49. Air dry specific gravity of petung bamboo, ampel bamboo, string bamboo, galah bamboo: 0,70; 0,71; 0,57; 0,61. Furnace dry specific gravity of petung bamboo, ampel bamboo, string bamboo, galah bamboo as follows: 0,72; 0,70; 0,62; 0,59. Of the four types of bamboo used, it is known that the axial direction, the presence of books and internodes do not have a significant effect on the moisture content and specific gravity.